Silica-supported bis(imino)pyridyl iron(II) catalyst: nature of the support-catalyst interactions - Ray, Saptarshi; Sivaram, Swaminathan (Polymer International, 2006)
Ethylene polymerizations were performed using silica-supported 2,6-bis[1-(2,6-diisopropylphenylimino) ethyl] pyridine iron(II) dichloride with methylaluminoxane (MAO) as co-catalyst. Silica was calcined at 600, 400 and 200 degrees C under vacuum for 8 h. The effect of calcination temperature of silica on the polymerization activity and the properties of the polymers obtained were examined. Catalyst-support interactions were examined by both a chemical method and XPS. It was observed that upon supporting the catalyst on the surface of silica, there is an increase in the binding energy of the metal center. However, no change in the metal binding energy was observed on supporting the catalyst to silica calcined at different temperatures. Ethylene polymerizations were performed using MAO as co-catalyst. Catalysts were also prepared by first pretreating silica with NIAO, followed by addition of the Fe(II) catalyst and contacting a complex of Fe(II) catalyst-MAO with silica previously calcined at 400 degrees C for 8 h. The results indicate that there is no chemical bonding between the support and the catalyst. (C). 2006 Society of Chemical Industry.
Keywords: bis(imino) pyridyl iron(II) complex; Polyethylene; silica; supported catalyst; XPS